Shock Treatment - Sharman, Jim; Molloy, Mike; Harper, Jessica; DeYoung, Cliff; O'Brien, Richard (Arrow Films, 2017)
It s not a sequel ... it s not a prequel ... it s an equal! Available on Blu-ray for the first time anywhere in the world, it is with absolute pleasure that Arrow Video presents "Shock Treatment" the criminally underrated sequel to "The Rocky Horror Picture Show"! Several years on from the events of the original Rocky, Brad and Janet Majors find their strained marriage put to the test on popular Denton TV show Marriage Maze. Poor Brad is heavily sedated and institutionalised, whilst Janet is given a radical makeover and primed for stardom. But what are the real motivations behind the kooky DTV crew and their enigmatic head-honcho, Farley Flavors? Featuring a host of familiar Rocky faces including Richard O'Brien and Patricia Quinn, alongside the likes of Jessica Harper, Barry Humphries and Rik Mayall not to mention a rocking, shocking score from Richard O'Brien and Richard Hartley "Shock Treatment" is the follow-up that's more than the equal of its predecessor. [Cover]
Keywords: Blu-Ray-Disc